Btn2 is involved in the clearance of denatured proteins caused by severe ethanol stress in Saccharomyces cerevisiae. Issue 8 (11th November 2019) - Kato, Sae; Yoshida, Masashi; Izawa, Shingo
ABSTRACT: Saccharomyces cerevisiae shows similar responses to heat shock and ethanol stress. Cells treated with severe ethanol stress activate the transcription of HSP genes and cause the aggregation of Hsp104-GFP, implying that severe ethanol stress as well as heat shock causes the accumulation of denatured proteins in yeast cells. However, there is currently no concrete evidence to show that severe ethanol stress causes protein denaturation in living yeast cells. In the present study, we investigated whether severe ethanol stress causes protein denaturation, and confirmed that a treatment with 10% (v/v) ethanol stress resulted in the accumulation of insoluble proteins and ubiquitinated proteins in yeast cells. We also found that increased denatured protein levels were efficiently reduced by the ubiquitin–proteasome system after the elimination of ethanol. Since our previous findings demonstrated that the expression of Btn2 was induced by severe ethanol stress, we herein examined the importance of Btn2 in protein quality control in cells treated with severe ethanol stress. btn2 ∆ cells showed a significant delay in the clearance of denatured proteins during the recovery process. These results provide further insights into the effects of severe ethanol stress on yeast proteostasis and the contribution of Btn2 to the efficient clearance of denatured proteins. Abstract : Severe ethanol stress causes the accumulation of denatured proteins in living Saccharomyces cerevisiae cells and Btn2 is involved in the efficient clearance of denatured proteins during the recovery process.